Challenges in Teaching Pronunciation: Secondary Level English Teachers’ Perspectives - Tiwari, Hari Prasad (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Correct pronunciation is a fundamental aspect of effective communication. It significantly enhances students’ overall speaking abilities. Nevertheless, teaching of pronunciation in the context of English as a Second / Foreign Language (EFL/ ESL) remains on the fringes and is marginalized within the academic syllabus and classroom dynamics, particularly in the secondary level schools of Nepal. This qualitative study aims at exploring the challenges faced by secondary level English teachers in teaching pronunciation. The research is based on the perspectives of six experienced secondary level English teachers who are engaged in teaching English at the secondary level. The researcher employed purposive sampling to select the participants. The study utilized semi-structured interview as the primary data collection technique. Each of the interviews was audio recorded and subsequently transcribed for meticulous analysis. The data was analysed employing thematic approach of qualitative data analysis The study highlighted nine different challenges which include priority issue, weak foundation at basic level, ignoring mispronunciations, time limit, teachers’ insufficient knowledge, copying peers, lack of instructional resources, lack of students’ reading habit, lack of exposure. The study suggests emphasizing pronunciation, increasing practice, enriching resources, promoting reading, and enabling real-world exposure to address the challenges.